Analisis Makna Kias Dalam Lagu “Pulang-For Revenge” - Intan Adriana Putri; Adinda Dewi Lestari; Shofiyatul Mukromiyah; Fikri Hakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The meaning of a lyric in a song can be interpreted with various meanings according to the theory used, one of which is using figurative meaning. This research is in the form of an analysis of the figurative meaning in the song Pulang by For Revenge. This analysis aims to find the figurative meaning in the song Pulang - For Revenge. Researchers in this case focus their research in terms of the semantic meaning of the figurative meaning in the song Pulang - For Revenge. The method used in this research is a qualitative-descriptive method. The data source for this research is the song Pulang - For Revenge. The data for this research is in the form of words that have figurative meanings found in the song Pulang - For Revenge. This research uses one instrument, namely the researcher himself. Based on research entitled Analysis of the Meaning of Figures in the Song Pulang - For Revenge, it was concluded that the Song Pulang - For Revenge contains many metaphorical meanings. The results of the analysis of the meaning of this song are interpreted from several points of view from researchers. Figurative meanings are found in the song Pulang - For Revenge with a total of 17 figurative meanings.